2021
DOI: 10.1016/j.eucr.2021.101578
|View full text |Cite
|
Sign up to set email alerts
|

Life-threatening abdominal compartment syndrome as a complication of supine super mini percutaneous nephrolithotomy, the first case report and literature review

Abstract: Abdominal compartment syndrome is a life-threatening complication of conventional percutaneous nephrolithotomy (PCNL), with few cases reported in different positions. We present the first case of abdominal compartment syndrome as a complication of supermini percutaneous nephrolithotomy (SMP) in The Galdakao-modified supine Valdivia position, possibly predisposing factors, diagnosis, and management. Although it is a challenging diagnosis and life-threatening condition, morbidity and mortality can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Khalil et al reported that risk factors for hydroperitoneum include an increased amount of irrigation fluid, operative time of more than 60-90 min, renal pelvis mucosal tear, and peritoneal scarring caused by previous ECIRS or PNL. 8 In this case, a minor peritoneal injury could have been overlooked. However, fluid overload should not be ruled out.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…Khalil et al reported that risk factors for hydroperitoneum include an increased amount of irrigation fluid, operative time of more than 60-90 min, renal pelvis mucosal tear, and peritoneal scarring caused by previous ECIRS or PNL. 8 In this case, a minor peritoneal injury could have been overlooked. However, fluid overload should not be ruled out.…”
Section: Discussionmentioning
confidence: 88%
“… 1 It is a rare complication as, to our knowledge, only nine cases have been previously reported (Table 1 ). 2 , 3 , 4 , 5 , 6 , 7 , 8 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations